Rap GTPase Interactor: A Potential Marker for Cancer Prognosis Following Kidney Transplantation - Fu, Qiang; Yang, Fan; Liao, Minxue; Feeney, Noel J.; Deng, Kevin; Serifis, Nikolaos; Wei, Liang; Yang, Hongji; Chen, Kai; Deng, Shaoping; Markmann, James F. (Frontiers in Oncology, 2019)
Post-transplant (post-Tx) kidney cancer has become the second-highest cause of death in kidney recipients. Late diagnosis and treatment are the main reasons for high mortality. Further research into early diagnosis and potential treatment is therefore required. In this current study, through genome-wide RNA-Seq profile analysis of post-Tx malignant blood samples and post-Tx non-malignant control blood samples (CTRL-Tx), we found Rap GTPase Interactor (RADIL) and Aprataxin (APTX) to be the most meaningful markers for cancer diagnosis. Receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) of the RADIL-APTX signature model was 0.92 (P < 0.0001). Similarly, the AUC of RADIL alone was 0.91 (P < 0.0001) and that of APTX was 0.81 (P = 0.001). Additionally, using a semi-supervised method, we found that RADIL alone could better predict malignancies in kidney transplantation recipients than APTX alone. Kaplan-Meier analysis indicated that RADIL was expressed significantly higher in the early stages (I and II) of kidney, liver, stomach, and pancreatic cancer, suggesting the potential use of RADIL in early diagnosis. Multivariable Cox regression analysis found that RADIL together with other factors (including age, stage III, stage IV and CD8+ T cells) play a key role in kidney cancer development. Among those factors, RADIL could promote kidney cancer development (HR > 1, P < 0.05) while CD8+ T cells could inhibit kidney cancer development (HR < 1, P < 0.05). RADIL may be a new immunotherapy target for kidney cancer post kidney transplantation